STUDI LITERATUR: ANALISIS MANAJEMEN BENCANA BANJIR DI KECAMATAN CIMANGGUNG KABUPATEN SUMEDANG - Edi Setiawan; Muftia Aulia Wahyuningsih; Nabila Azmi; Dewi Maharani (LPPM UNSAP, 2026)
This study aims to analyze flood disaster management (case study: Cimanggung sub-district, Sumedang regency). The research method used in this writing is descriptive, which aims to describe the condition/symptoms of a particular group and describe certain relationships between one symptom and another. The research locus is in Cihanjuang Village, Sindangpakuon Village, Sindanggalih Village, and Sukadana Village which are located in Cimanggung sub-district, Sumedang regency. Sources and types of data collection, namely using secondary data sources obtained from journals and news portals. The data analysis technique used by the author is qualitative descriptive analysis. Based on the results and discussion, flood disaster management in Cimanggung sub-district, Sumedang regency is quite good. However, in its implementation, it still faces several obstacles. The efforts that can be made to overcome these obstacles are strengthening coordination between stakeholders through multi-party forums, sustainable infrastructure development and maintenance, and community education and empowerment.